(untitled) - Davidson, George (Singapore, 2003)
Verbs and Tenses aims to help english language learners through the difficulties they may encounter when they are trying to understand finite and non-finite verbs, lexical and auxiliary verbs, the modal verbs, the meanings and uses of the different tenses, and so on. The book is comprehensive in coverage and explains clearly and concisely the relevant rules and terminology. The explanations are illustrated by many examples.
Keywords: English language,English language,Tiếng Anh,Tiếng Anh; Verb,Tense,Động từ,Thì động từ